The Prevalence of Gram-Negative Microorganisms Isolated from VentilatorAssociated Pneumonia Patients in the Intensive Care Units of Southwest of Iran - Saeed Mehralinejadian; Mandana Izadpanah; Farhad Soltani; Sepideh Sayadi; Maryam Aghakouchakzadeh (Research Center for Rational Use of Drugs (RCRUD), 2020)
Increasing microbial resistance is a severe threat to global public health. One of the most common diseases in the intensive care unit is ventilator-associated pneumonia. This study was carried out from January to March 2018, at the Golestan Hospital of Ahvaz. Patients with ventilator-associated pneumonia were included in the study. The prevalence of resistant gram-negative microorganisms was studied through reported laboratory antibiogram results of cultures. Based on the results of the study, From 373 hospitalized patients, 38 (10.2%) were diagnosed with VAP. From the 57 respiratory cultures performed, overall 90 microorganisms were isolated, from which Enterobacter with 36 cases (39.5%) and E.Coli with 28 cases (30.7%) was most frequently compared to other organisms. Of the 90 organisms responsible for the infection, 43 cases (47.2%) were MDR microorganisms and 47 (51.6%) were XDR microorganisms. Enterobacter and E.Coli were the most prevalent MDR microorganisms with 17 cases (39.5%) and 13 (30.2%), respectively. Also, these two microorganisms were the most abundant XDR microorganisms with 19 cases (40.4%) and 15 (31.9%), respectively. The results show the requirement of robust antibiotic monitoring and the optimization of antibiotic use in order to prevent the progression of antibiotic resistance in these units.